MANAJEMEN PENGEMBANGAN MUTU PENDIDIKAN SEKOLAH DASAR BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SD NEGERI AIR LOUW - Grace Lisapaly; Patrisius Rahabav; Tanwey Gerson Ratumanan (Universitas Nusa Cendana, 2025)
Improving the quality of basic education requires schools to develop a management system that is adaptive to the development of Information and Communication Technology (ICT). The use of ICT not only plays a role in learning, but also becomes a strategic instrument in planning, implementation, and evaluation and control of the quality of education. This study aims to analyze the management of the ICT-based education quality development system at Air Louw State Elementary School. The research uses a qualitative approach with a case study design. Data collection was carried out through in-depth interviews, observations, and document analysis of school principals, teachers, school operators, and quality management teams. The data was analyzed using thematic analysis to identify key patterns and themes related to ICT-based education quality management. The results of the study show that the use of ICT in education quality planning allows schools to prepare visions, work programs, and School Activity Plans and Budgets (RKAS) based on digital data in a more objective and measurable manner. At the implementation stage, ICT supports administrative governance, learning, and assessment, although there are still variations in utilization due to limited digital facilities and competencies of human resources.